Free vibration and damping analysis of porous functionally graded sandwich plates with a viscoelastic core. (15th July 2020) - Zhang, Yantao; Jin, Guoyong; Chen, Mingfei; Ye, Tiangui; Yang, Chuanmeng; Yin, Yaowei
Abstract: Free vibration and damping analysis of porous functionally graded (FG) sandwich plates are presented based on a modified Fourier-Ritz method. The sandwich plate is composed of a viscoelastic core and two porous FG face layers. A complex elasticity modulus is employed to describe the viscoelastic core. Material properties of the porous FG face layer are described continuously across each face thickness according to a volume fraction index and a porosity coefficient. The distribution of porosities within the face layers is formulated either evenly or unevenly. The displacements are constructed by the first-order shear deformation theory combined with the modified Fourier method. The free vibration and damping analysis of a porous single-layered plate and a non-porous sandwich plate are then conducted to exhibit the capability and accuracy of the developed method. The obtained results are in good agreement with those in literature. Finally, a series of parametric analyses are investigated in detail, in which boundary condition, power-law index, porosity coefficient, geometric dimension and material loss factor are taken into consideration. It is noted that the porosities within the FG face layers have significant effects on the natural vibration and damping performance of porous FG sandwich plates.